1 - Aux origines de la catastrophe économique de l'Afrique - Amin, Samir (Africa Development, 1995)
Development policies in the Third-World — from the 'colonial development' to the Bandoung 'Nationalist Project of Modernisation' have shown their limits. This is currently illustrated by the restraint cf the Lome Agreements and the impossibility of a globalisation through the market. Today, Africa is living a new era of polarisation as a result of the position it occupies in the new technological, nuclear and financial arena, and in terms of access to natural resources and information. The author calls for a pluricentric, humanist and socialist globalisation project, one which challenges the existing monopolies.